THE INFLUENCE OF BRAND IMAGE AND BRAND EXPERIENCE ON BRAND LOYALTY WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE: CASE STUDY ON TOKOPEDIA CONSUMERS IN THE JABODETABEK AREA - Prabawati, Erika; Edy Handoyo, Sarwo (Penerbit Lafadz Jaya, 2023)
Brand loyalty can determine whether e-commerce is able to survive or not in the market. The bad brand image of e-commerce will indirectly reduce consumer confidence to use e-commerce. E-commerce must also be able to create a comfortable brand experience, with the aim of increasing interest in using e-commerce in a sustainable manner so as to increase brand loyalty. The purpose of this study was to analyze the effect of brand image and brand experience on brand loyalty with customer satisfaction as an intervening variable. Consumers of Tokopedia aged between 15-30 years in Jabodetabek are the population of this study. Samples were taken as many as 100-200 people. This research uses non-probability sampling with purposive sampling technique. Primary data was collected by using a questionnaire with a Likert scale and secondary data by interview. This study uses AMOS to analyze research data. The results of this research are (a) Brand Image has a positive effect on Brand Loyalty, (b) Brand Experience has a positive effect on Brand Loyalty, (c) Brand Image has a positive effect on Customer Satisfaction, (d) Brand Experience has a positive effect on Customer Satisfaction, (e) Customer Satisfaction has a positive effect towards Brand Loyalty. Based on the research results, all research hypotheses are accepted with the best hypothesis, namely the more positive the promotion, the more positive brand loyalty will be.